Unlocking maize crop productivity through improved management practices in Northern Tanzania - Kihara, Job Maguta; Kizito, Fred; Jumbo, M.; Kinyua, M.; Bekunda, Mateete A. (African Journal of Food, Agriculture, Nutrition and Development, 2020)
Addressing the problem of low crop productivity and food insecurity can be accelerated through community-centered implementation of good agricultural management practices. This study was conducted in Babati, Northern Tanzania. The objective of the study was to determine nitrogen (N)and phosphorus (P)application requirements for maize,and demonstrate economically viable best bet yield-improving management technologiesunder three ecozones namely; ‘low elevation low rainfall’, ‘medium elevation high rainfall’ and ‘medium elevation low rainfall’ ecozone. Two sets of trials were conducted: N (0, 45, 90, 120 and 150 kg ha-1) and P (0, 15, 30, 40 kg ha-1) response trials in 16 representative fields in three seasons of 2013/14, 2014/205 and 2015/16 and; demonstrations trials in 8 farmer-selected fields in 2015/16 season. Combined N and P application increased maize yields by 32 to 62% over single nutrient applications.In the medium elevation low rainfall ecozone, 60-86%yield response to nitrogenwas observed.Largely, modest applications of 50 kg N ha-1and 20 kg P ha-1resultedin profitable (marginal rate of return (MRR) of 2.4 to 3.0) yield increases of upto 214% over the farmers practice (unfertilized), varying with variety and ecozone. The source of P (DAP or Minjingu Mazao) had little influence on maize productivity except under low altitude low rainfall where Minjingu Mazao is unprofitable. Farmer rankings and agronomic indices showed new maize hybrids namely Meru H513, Meru H515, and SC627 as a priority across the ecozones; Mams H913 is suitable mainly in medium elevation low rainfall ecozone. The conclusion is that the use of new maize hybrids and appropriate rates of locally available N and P nutrient sources can bridge existing yield gaps and reduce food insecurity. Technologies from community-driven research in development are easily adopted by a large number of farmers and could result in quick, yet lasting productivity gains.